Gender Inequalities in the Education of the Second Generation in Western Countries. (July 2014) - Fleischmann, Fenella; Kristen, Cornelia; ,; Heath, Anthony F.; Brinbaum, Yaël; Deboosere, Patrick; Granato, Nadia; Jonsson, Jan O.; Kilpi-Jakonen, Elina; Lorenz, Georg; Lutz, Amy C.; Mos, David; et al.
Drawing on comparative analyses from nine Western countries, we ask whether local-born children from a wide range of immigrant groups show patterns of female advantage in education that are similar to those prevalent in their host Western societies. We consider five outcomes throughout the educational career: test scores or grades at age 15, continuation after compulsory schooling, choice of academic track in upper-secondary education, completion of upper secondary, and completion of tertiary education. Despite great variation in gender gaps in education in immigrants' origin countries (with advantages for males in many cases), we find that the female advantage in education observed among the majority population is usually present among second-generation immigrants. We interpret these findings in light of ideas about gender role socialization and immigrant selectivity.